Konsequenzen der Strategiedebatte für die Produktion - Krcal, Hans-Christian (Discussion paper series, 2007)
The paper shows how traditional organizational structures within the production sector, such as quality circles, learning groups ("Lernstatt") and project teams reflect the constructivist and postmodern concepts of strategic management with their wide ignorance of purely plan deterministic aspects of strategy.
Keywords: Arbeitspapier; Graue Literatur